The added value of orthotic management in the context of multi-level surgery in children with cerebral palsy - Schwarze, Martin; Block, Julia; Alimusaj, Merkur; Heitzmann, Daniel; Putz, Cornelia; Dreher, Thomas; Wolf, Sebastian Immanuel (Gait & posture, 2019)
Background - Treatment of cerebral palsy includes an interdisciplinary concept and in more severe cases the well-established multi-level surgery (MLS). Different kinds of orthoses are typically part of postoperative treatment but there is a lack of knowledge about their additional benefit. - Research question - Do ankle foot orthoses lead to an additional, measurable improvement of gait after MLS? - Methods - 20 children with bilateral spastic cerebral palsy (9 retrospective, 11 in a postoperative clinical routine) were included. All had a preoperative gait analysis before MLS. Postoperatively, they were fitted with different ankle foot orthoses (AFO), depending on their individual needs. Dynamic ankle foot orthoses (DAFO), combined DAFO with additional dynamic, elastic shank adaptation (DESA) and ground reaction force AFOs (GRAFO) were used. Patients underwent a second gait analysis 1.5 (± 0.6) years postoperatively barefoot and with orthoses. Data analysis included testing for normal distribution (Shapiro-Wilk-Test) and further nonparametric statistical testing on basis of a Wilcoxon Single-Rank Test. - Results - The operation produced changes in the hip, knee and ankle joint, and the pelvis. Spatiotemporal parameters showed significant changes due to additional use of the orthoses. Further, additional kinematic changes occurred at the hip, knee and ankle joint as well as the foot. The Gillette Gait Index (GGI) improved significantly by supplementary orthoses, but not by surgery alone. The Gait Profile Score (GPS) and Gait Deviation Index (GDI) rather showed changes due to the surgery. - Significance - MLS significantly improves GPS and GDI more than a year after surgery, which can be interpreted as an improvement in gait pattern. In contrast, the GGI is improved by additional postoperative orthotic treatment, which implies that walking ability itself has improved, rather than the gait pattern. Orthoses show a positive additional effect on surgical results at different anatomical levels. Spatiotemporal parameters are positively influenced solely by additional orthotic support.
Gesehen am 22.11.2019